CSF‐plasma biomarker profiles from BioFINDER MCI patients using the same technology. (20th December 2022) - Vanmechelen, Eugeen; Dewit, Nele; Vanbrabant, Jeroen; Mauroo, Kimberley; Stoops, Erik; Stomrud, Erik; Janelidze, Shorena; Hansson, Oskar
Abstract: Background: Technological advancements have made it possible to translate changes in cerebrospinal fluid (CSF) into promising plasma biomarkers, such as the amyloid β ratio (Aβ42 /Aβ40 ) and phosphorylated tau (p‐tau), but comparing CSF and plasma levels were often based on different technologies. Combining biomarkers have demonstrated a superior performance of the ratio of p‐tau over Aβ42 to discriminate Aβ‐positive (Aβ+) and Aβ‐negative (Aβ‐) groups in CSF, especially using automated immunoassay platforms, but has not yet been studied in plasma. Method: In a subset of 155 MCI individuals of the BioFINDER‐1 study, from which 84 paired CSF‐plasma were available for analysis, Aβ42, Aβ40 and p‐tau181 were determined using ADx Simoa assays (Thijssen et al, 2021; Bayoumy et al, 2021) in both fluids using the appropriate dilution factors. Result: The intra‐run %CV was between 1.7 and 2.6% for both Aβ markers in CSF and plasma and was higher in plasma for p‐tau181 than in CSF with respectively 10.5 and 1.7%. Both CSF Aβ42, Aβ40 and Aβ42 /Aβ40 were highly correlated to CSF Aβ measurements using the MSD platform: spearman ρ of 0.845; 0.828; and 0.882 for respectively for Aβ42, Aβ40 and their ratio. In the paired CSF‐plasma analysis the strongest correlation was found for p‐tau181/Aβ42 and p‐tau181 with respectively a ρ=0.689 and 0.616 and a significantly weaker correlation for Aβ42 /Aβ40 ratio (ρ=0.283). Defining an Aβ+ and an Aβ‐ subgroup by using a previously verified CSF Aβ42 /Aβ40 of 0.07, all plasma biomarkers could differentiate Aβ+ and Aβ‐ individuals. The highest AUC was observed for p‐tau181/ Aβ42, 0.806, significantly (p=0.0465) higher than p‐tau181 (0.784) and the Aβ42 /Aβ40 (0.688)(Fig 1). Conclusion: Correlations in paired CSF‐plasma samples using the same technology are significant, but weak for some of them suggesting a different turnover of these analytes in these fluids. Nevertheless combining both well‐established pathological markers in plasma, p‐tau and Aβ42, may be a simple way to enhance early diagnosis based especially if automated immunoassay platforms are envisaged.